A cyclic plasticity model for secondary hardening due to strain-induced martensitic transformation. (May 2021) - Bemfica, Cainã; Castro, Fábio
Abstract: A model for secondary cyclic hardening due to strain-induced martensitic transformation in metastable austenitic stainless steels is proposed. The model is built on an Armstrong–Frederick type kinematic hardening framework. Secondary hardening is described by relating the size of the limiting surface of each backstress to an evolution rule for the martensite content. A memory surface is used to account for the influence of the plastic strain amplitude on martensitic transformation. The model properly estimated the stress response of three austenitic stainless steels (types 304/304L, 321, and 348) subjected to strain-controlled axial, torsional, and proportional loading. The characteristics of the model, the determination of material constants, and suggestions for future research are discussed.